2012
DOI: 10.1111/j.1399-6576.2011.02605.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on maintenance of intense neuromuscular block with rocuronium

Abstract: The times from rocuronium injection to reappearance of the first response to PTC stimulation are approximately twofold longer and more variable in older than younger patients. Hence, the dosing interval of rocuronium should be adjusted using neuromuscular monitoring when maintaining intense neuromuscular block, especially in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…However, when the two groups were compared, it was revealed that it was greater for vecuronium than cisatracurium. Similarly, the duration of intensive block after a single intubation dose of rocuronium had a wider range in patients over 70 years of age than it did in younger subjects, between the ages of 20−60 [24].…”
Section: Benzylisoquinoline Derivativesmentioning
confidence: 90%
See 1 more Smart Citation
“…However, when the two groups were compared, it was revealed that it was greater for vecuronium than cisatracurium. Similarly, the duration of intensive block after a single intubation dose of rocuronium had a wider range in patients over 70 years of age than it did in younger subjects, between the ages of 20−60 [24].…”
Section: Benzylisoquinoline Derivativesmentioning
confidence: 90%
“…mean time to response to a single stimulation preceded with tetanic stimulus, i.e. a post-tetanic count (PTC) = 1 [24].…”
Section: Aminosteroidsmentioning
confidence: 99%
“…First, there is an increase in the duration of action of rocuronium with age. A study conducted by Furuya et al concluded that the duration of time taken for the appearance of posttetanic count (PTC) was twofold longer and variable in older as compared to younger individuals [11]. Secondly, there is a prolongation of rocuronium action in the female gender as compared to males [12].…”
Section: Discussionmentioning
confidence: 99%
“… 29 This prolongation may be as much as a twofold increase, from 31 minutes in younger patients to 51 minutes in the elderly. 37 Therefore, in elderly patients, extra doses should be administered with care, only after the reappearance of train-of-four response.…”
Section: Pharmacology Of Nmbas In the Elderlymentioning
confidence: 99%
“…Variations in body habitus and composition of the body of the elderly may result in an overdosing due to the altered pharmacokinetics of NMBAs caused by, as previously mentioned, increased fat, decreased muscle mass, and lower Vd. 37 …”
Section: Pharmacology Of Nmbas In the Elderlymentioning
confidence: 99%